Intensity of tennis match play. Issue 5 (21st April 2006) - Fernandez, J; Mendez-Villanueva, A; Pluim, B M
Abstract : This review focuses on the characteristics of tennis players during match play and provides a greater insight into the energy demands of tennis. A tennis match often lasts longer than an hour and in some cases more than five hours. During a match there is a combination of periods of maximal or near maximal work and longer periods of moderate and low intensity activity. Match intensity varies considerably depending on the players' level, style, and sex. It is also influenced by factors such as court surface and ball type. This has important implications for the training of tennis players, which should resemble match intensity and include interval training with appropriate work to rest ratios.